Penatalaksanaan Nyeri Pada Asuhan Keperawatan Keluarga Tn.S Dengan Hipertensi Di Puskesmas Mojolaban - ANGGITA SAPUTRI, RENA, Agus Sudaryanto, S.Kep., Ns., M.Kes (2016)
The value of hypertension's case in Indonesia has increased from year to year. This case increase because the factor of age increased and unhealthy life style. Hypertension becomes a killer disease number one in Indonesia because it's not make symptomps and special indication. The common symptoms who emerge on patient of hypertension is headache. Headache emerge because the pressure of intrakranial was increase, it will have impact on the death of heart cell. If left away, the pain will increase and make a complication like a stroke, a coronary heart, or failure kidney. The handling of hypertension was splits in two, that is pharmacology therapy and non pharmacology. One of the theraphy non pharmachology who have an effective ability to fade muscle tension and give a relax sensation. Beside the theraphy who has given, the support of family also have a role immportant in treatment of patients of hypertension.The purpose of writing a scientific paper was to knowed the nursing problems in patients with hypertension and progressive muscle relaxation techniques taught as a therapy for pain management in patients with hypertension. The method was used descriptive methode with study case approachment was scientificed methode who have character to collect the data, analyze the data, dan draw the conclusion in the Public Health of Mojolaban. To obtained the data the writer used some methode, that was collected the data use observation, a physical examination, interview, documentation study from the journal or book. The results obtained in patients with hypertension appeared a major problem feeling comfortable disorders ( headache ) . To addressed the problem of progressive relaxation therapy techniques . This therapy was very effective in reducing pain evaluation because otherwise managed to reduce the pain scale and capable of controlling blood pressure . So the conclusion of this paper was progressive relaxation being non-pharmacological therapy appropriated and practical for review lowering blood pressure pain and control .